Prevalence and correlates of elder abuse among older women in rural and urban communities in Southwestern Nigeria. (2012)
Elderly women face the same health, economic, and social issues that all elderly people face, but often encounter more challenges compared with men and are more prone to abuse. Elder abuse has hitherto been uncharacterized among women in South Western Nigeria. A cross-sectional survey was conducted to describe the prevalence, patterns, and factors associated with elder abuse among elderly women in Nigeria. The abuse of elderly women is quite prevalent in the two communities studied, especially physical abuse. Positive predictors of elder abuse were urban dwelling, financial dependency, and a high level of educational attainment. Appropriate interventions should be targeted toward reducing the occurrence.